Review of atrazine sampling by polar organic chemical integrative samplers and Chemcatcher. (7th June 2018) - Booij, Kees; Chen, Sunmao
Abstract: A key success factor for the performance of passive samplers is the proper calibration of sampling rates. Sampling rates for a wide range of polar organic compounds are available for Chemcatchers and polar organic chemical integrative samplers (POCIS), but the mechanistic models that are needed to understand the effects of exposure conditions on sampling rates need improvement. Literature data on atrazine sampling rates by these samplers were reviewed with the aim of assessing what can be learned from literature reports of this well‐studied compound and identifying knowledge gaps related to the effects of flow and temperature. The flow dependency of sampling rates could be described by a mass transfer resistance model with 1 (POCIS) or 2 (Chemcatcher) adjustable parameters. Literature data were insufficient to evaluate the temperature effect on the sampling rates. An evaluation of reported sampler configurations showed that standardization of sampler design can be improved: for POCIS with respect to surface area and sorbent mass, and for Chemcatcher with respect to housing design. Several reports on atrazine sampling could not be used because the experimental setups were insufficiently described with respect to flow conditions. Recommendations are made for standardization of sampler layout and documentation of flow conditions in calibration studies. Environ Toxicol Chem 2018;37:1786–1798. © 2018 SETAC